Is There a Relationship Between Microvascular Complications and the Severity of Type 2 Diabetes Mellitus? - Çatan, Funda; Bener, Abdülbari; Öztürk, Mustafa (Kare Publishing, 2020)
Objective: The aim of this study was to determine the relationship between microvascular Type 2 diabetes mellitus (T2DM) complications and the severity and duration of diabetes in the light of sociodemographic and lifestyle variables. Materials and Methods: This is a prospective cohort study based on 899 (527 females, 372 males) patients with T2DM aged 25–70 years. Patient information including socio-demographic variables; body mass index (BMI); lifestyle habits and duration of diabetes; treatment of diabetes; values for hemoglobin A1c (HbA1c); development of diabetes complications; and the presence of neuropathy, nephropathy, and retinopathy were recorded. A univariate and multivariate statistical analysis were performed. Results: Significant differences were found between diabetics with HbA1c ≤7 and >7 in terms of the education level, occupation, household income, duration of diabetes, the number of children, smoking, physical exercise, eating fast food, control regularity, and diabetes education. A total of 17.1% of patients had diabetic retinopathy, 17.0% had neuropathy, and 13.7% had nephropathy. Among diabetics, 2.3% had three microvascular complications, whereas 66.6% had none of them. The prevalence of diabetes complications was lower in patients who had good glycemic control than those who had poor glycemic control. Furthermore, the highest reduction in the level of HbA1c was for sulfonylurea usage. Conclusion: A high prevalence of diabetes complications is a burden for both the patients and the health care system. Screening, early diagnosis, management of the glucose level, and the follow-up may result in delayed diabetes complications.
Keywords: microvascular complications; Medicine (General); microvascular complications.; R5-920; Microvascular Complications; diabetes; Diabetes; Severity Of Type 2 Diabetes; severity of type 2 diabetes; 3. Good health